The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/jsfa.7485
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the potential beverage quality of coffee produced in the Zona da Mata, Minas Gerais, Brazil

Abstract: The production site's position and altitude are the primary variables that influenced the coffee quality. The study area has micro-regions with grades ranging from 80 to 94. These areas have the potential for producing specialty coffees. © 2015 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
10

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 23 publications
1
29
0
10
Order By: Relevance
“…The increase in the efficiency of agricultural managements must contemplate the spatial and temporal variability existing at the field (Silva et al, 2015). Thus, it is possible to optimize the use of agricultural inputs with reduction of economic and environmental risks, obtaining greater profitability and quality of the products (Corwin & Lesch, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The increase in the efficiency of agricultural managements must contemplate the spatial and temporal variability existing at the field (Silva et al, 2015). Thus, it is possible to optimize the use of agricultural inputs with reduction of economic and environmental risks, obtaining greater profitability and quality of the products (Corwin & Lesch, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This observation can be corroborated by the research of Silva et al (2016), in which it was evaluated the influence of climatic conditions in the region of Matas de Minas on the quality of the coffees of 20 municipalities in the region, in which the authors concluded that even in the same or similar climatic conditions the samples presented different scores for the quality of the drink.…”
Section: Sensory Profile Of Pulped Coffees (Cd) and Natural Coffees (mentioning
confidence: 65%
“…Both studies found that high altitude and annual rainfall under 1500 mm were favourable factors of coffee sensory quality (Decazy et al, 2003), east-facing slopes gave coffee beverages generally superior attributes (Avelino et al, 2005), and shade also positively affected coffee beans size and coffee beverage quality (Vaast et al, 2006). This was confirmed by Silva et al (2016) who recently found that the position and altitude of the fields are the main variables that influence coffee quality. Sanchez et al (2013) assessed the effect of soil properties on yield and quality of coffee and found that coffee grown on soils with high clay and available iron contents, and low pH and base saturation, provided the highest yield and best sensory quality.…”
Section: Introductionmentioning
confidence: 69%
“…Coffee is a specialty crop whose diversity in production systems allows products with defined attributes for different markets (Silva, de Queiroz, Ferreira, Correa, & Rufinod, 2016). Production of high quality Arabica coffee is considered to depend on three main factors: the genetic resource, environmental conditions, and management (Bosselmann et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation